Concreto resfriado: uma análise comparativa entre as temperaturas do concreto resfriado e o convencional - Oliveira, Naieide Batista de (Universidade Federal Rural do Semi-Árido, 2017)
The Brazilian semi - arid is known as the region of frequent events of "drought", the climate of the territory and marked by values of lower rainfall indices, wind variations and low values. When a need arises for manufacturing high-density concrete parts, their high temperature values together with environmental factors become considerable points for the possible advent of structural problems, such as the appearance of pathological concrete parts, if they are: preformed or molded in loco. Therefore, the need to study these techniques and to enable their use, in order to moderately control the heat of hydration, avoiding future problems, guaranteeing a resistance and a durability of the structure. One type of procedure is used by kneading the concrete into the form of ice in flakes. Its purpose is to reduce as heat rates emitted by reactions, controlling-like through the temperature of the ice, allowing a conclusion of the reactions without compromising a structure. Therefore, a present research carried out a molding of two blocks of concrete mass: one of cooled concrete using low heat of Portland cement cement (CPIV), and the other of conventional concrete with the use of Portland cement of initial resistance CPV), with the objective of evaluating the whole process of thermal variations due to its hydration during 28 days. After the presentation of values, it can be noticed that the cooled concrete presented significant advantages compared to the conventional concrete, as: low value of launch temperature, control in the addition of temperatures, and temperature values lower than the conventional concert. Based on all the factors, it was possible to verify that the use of the mass cooled concrete does in fact present thermal advantages when compared to other types of concrete, especially when it is used in regions with semi-arid characteristics and high density parts.
Keywords: Concreto massa; Calor de hidratação; Fissuras; Concrete mass; Heat of hydration; Fissures; ENGENHARIAS::ENGENHARIA CIVIL